The Role of Artificial Intelligence and Digital Literacy in Enhancing Employee Effectiveness and Efficiency in the Economic Sector - Niam, Anwar; Insani, Maulana Raya; Sukmawati, Sukmawati; Hike, Fridman (Journal of Economics and Management, 2025)
The advancement of technology, particularly artificial intelligence (AI) and digital literacy, has brought significant changes to the workforce, including the economic sector. This study aims to analyze the role of AI and digital literacy in enhancing employee effectiveness and efficiency. AI enables the automation of routine tasks, optimization of decision-making, and increased productivity through faster and more accurate data analysis. Meanwhile, digital literacy is a crucial factor for employees to adapt to new technologies and utilize digital tools optimally. This research employs a qualitative method with a literature review approach to examine the impact of AI implementation and digital literacy levels on employee performance. The findings indicate that a combination of AI and digital literacy can improve work efficiency, reduce administrative burdens, and support innovation in business processes. However, challenges such as human resource readiness and adaptation to technological changes remain significant barriers. Therefore, strategies to enhance digital competencies for employees and policies supporting AI integration in the workplace are needed.